Expanding Understanding of Motherhood Penalty: How Gaps in Family Policies Contribute to Gaps in Old-Age Earnings in Russia - Kingsbury, Marina A. (Frontiers in Sociology, 2019)
This study identifies policy shortcomings in the structure of Russian family policies and old-age pension calculations and shows how gaps in coverage contribute to the motherhood penalty in Russia. I first show that shortages in access to affordable childcare contribute to mothers’ involuntary labor market inactivity leading to loss in earnings. I then discuss how childcare breaks are treated in terms of pensionable experience and present simulation of pension outcomes to show the negative impact of long childcare breaks on mothers’ pensions.